Group III secreted phospholipase A(2) transgenic mice spontaneously develop inflammation - Sato, Hiroyasu (Portland Press Ltd., 2009)
PLA(2) (phospholipase A(2)) group III is an atypical sPLA(2) (secretory PLA(2)) that is homologous with bee venom PLA(2) rather than with other mammalian sPLA(2)s. In the present paper, we show that endogenous group III sPLA(2) (PLA2G3) is expressed in mouse skin and that Tg (transgenic) mice overexpressing human PLA2G3 spontaneously develop skin inflammation. Pla2g3-Tg mice over 9 months of age frequently developed dermatitis with hyperkeratosis, acanthosis, parakeratosis, erosion, ulcer and sebaceous gland hyperplasia. The dermatitis was accompanied by infiltration of neutrophils and macrophages and by elevated levels of pro-inflammatory cytokines, chemokines and prostaglandin E(2). In addition, Pla2g3-Tg mice had increased lymph aggregates and mucus in the airway, lymphocytic sialadenitis, hepatic extramedullary haemopoiesis, splenomegaly with increased populations of granulocytes and monocytes/macrophages, and increased serum IgG(1). Collectively, these observations provide the first demonstration of spontaneous development of inflammation in mice with Tg overexpression of mammalian sPLA(2).